Combined travel forecasting models - formulations and algorithms - Hillel Bar-Gera; David Boyce (European Regional Science Association (ERSA), 2002)
Consistent transportation forecasting models that combine travel demand and network assignment are receiving more attention in recent years. A fixed point formulation for the general combined model is presented. Measures for solution accuracy are discussed. An origin-based algorithm for solving combined models is proposed. Experimental results demonstrate the efficiency of the algorithm in comparison with prevailing alternatives.
Keywords: 330